Research on Non-suicidal Self-Injury in Adolescents : Literature review - Murtonen, Eevi (My University, 2026)
The purpose for this literature review is to examine the state of research on possible trend changes regarding non-suicidal self-injury (NSSI) among 13–18-year-old adolescents within community-based populations. Non-suicidal self-injury (NSSI) is defined as deliberate, self- inflicted harm to one’s own body without the intent of suicide and has been identified as a separate phenomenon from other forms of self-injurious behaviors, such as suicidal ideation, attempts, or deaths. Articles for this literature review were collected from three databases (Pubmed, Embase, PsycInfo) alongside with a later manual search and overlook of references from the selected articles. The search focused on population-based time-trend studies of NSSI in adolescents in which data were collected through anonymous self-reporting questionnaires. Out of 1,002 originally found articles only one met all priorly established criteria and was chosen to be the leading article for this review. Additionally, three previously excluded articles with the greatest potential of presenting findings on trend changes in NSSI and overall mental health in adolescents were chosen to act as supporting articles. According to current literature, the lifetime prevalence of NSSI and its association with suicidality have remained relatively stable over time, although a slight increase of NSSI was observed during the global COVID19-pandemic, especially among the female population. The near absence of studies examining trend changes solely on NSSI outside of a pandemic leaves its current trajectory largely unknown. Despite some controversy regarding trends, the reviewed literature consistently identifies NSSI as a significant health concern highlighting the need for its early preventive interventions.
Keywords: Non-suicidal Self-injury, Adolescents, Time-trend change studies